The Influence of Vehicle Maintenance Conditions on Chosen Electric Parameters of Starter During Combustion Engine Start-Up - Pawel Drozdziel (Communications - Scientific letters of the University of Zilina, 2006)
Necessary mechanical energy needed for initiation of self-dependent combustion engine work is transferred by crankshaft driving using an electrical starter. Changes of values of the static resistant moment and start-up resistant moment in the engine influence current input by the electric starter during start-up of the combustion engine. Overloads observed in the vehicle electric power system are the results of high value of current intensity input by the electric starter. It seems very important to find the answer how the vehicle maintenance conditions influence the chosen working electric parameters of the starter during the combustion engine start-up. This article presents the results of investigations of starting working electric parameters during a combustion engine start-up, made during the vehicle maintenance.